Analisis Ideologi Kolonialisme Dalam Novel Bumi Manusia Karya Pramoedya Ananta Toer Kajian Pos Kolonial - Sri Wahyuni Ningsih; Mila Misrohatul Karomah; Erfania Nabila; Mas’odi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
The importance of literary works in reflecting socio-political conditions during the colonial period, especially in the context of cultural resistance in a novel